Reflections on the readings of Sundays and feasts: September-November 2023 - Sobb, Joseph (The Australasian Catholic record, 2023)
Twenty-Second Sunday in ordinary time (3 September 2023) (Jer 20:7-9; Rom 12:1-2; Matt 16:21-27) The second reading is taken from the final section of Paul's letter to the Romans. After the long discussion/discourse on salvation by faith in Christ (Rom 1-8), followed by a reflection on the relationship between this salvation and the promises to the people of Israel in the Old Testament (Rom 9-11), Paul moves into a kind of practical application, issuing a series of exhortations concerning how we are to live our "new life in Christ". Today's passage, the first of three extracts, introduces a unifying theme of τepsilońlambdaepsilonιος/mature/perfect, echoed in another letter (1 Cor 2:6; 14:20) and evoked in another epistle (Eph 4:13).